Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.ygeno.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of codon usage bias across Leishmania and Trypanosomatids to understand mRNA secondary structure, relative protein abundance and pathway functions

Abstract: Understanding the variations in gene organization and its effect on the phenotype across different Leishmania species, and to study differential clinical manifestations of parasite within the host, we performed large scale analysis of codon usage patterns between Leishmania and other known Trypanosomatid species. We present the causes and consequences of codon usage bias in Leishmania genomes with respect to mutational pressure, translational selection and amino acid composition bias. We establish GC bias at w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 46 publications
(73 reference statements)
1
19
0
Order By: Relevance
“…There have been many hypotheses on the cause and consequence of the usages of codons and codon pairs, such as gene expression level [85][86][87][88][89][90][91], mRNA structure [92-98], protein abundance [98][99][100][101], and mRNA/protein stability [102][103][104]. Here we demonstrated that the genetic code is nearly optimal for frameshift tolerance.…”
Section: Discussionmentioning
confidence: 66%
“…There have been many hypotheses on the cause and consequence of the usages of codons and codon pairs, such as gene expression level [85][86][87][88][89][90][91], mRNA structure [92-98], protein abundance [98][99][100][101], and mRNA/protein stability [102][103][104]. Here we demonstrated that the genetic code is nearly optimal for frameshift tolerance.…”
Section: Discussionmentioning
confidence: 66%
“…The notion of gene expression by CAI values was proposed for a long time ago, however, in recent years, the methods have been widely used to qualitatively assess high-level expression genes in prokaryote and eukaryote [38,39,40,41]. Fast development of the whole-genome analysis technologies, especially whole genome sequencing as well as proteomics has made it possible to compare computational data of codon usage and expression ability with experimental evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The predominant impact of selection pressure on CUB of tyrosinase genes was further supported by plots between ENC and GC 3 , and between ENC and CAI (Fig. 2) [20,31]. …”
Section: Discussionmentioning
confidence: 88%
“…(a=0.0580; R=0.2391) and S. mediterranea (a=0.0508; R=0.1690). Taken together, these data strongly suggested that the selection pressure, such as translational selection rather than mutational bias, was the main force governing bias in nucleotide composition of tyrosinase codons (refer [31] and references therein), even though it was apparent that mutational bias also provided significant force causing the bias at least in the C. sinensis and O. viverrini genes. The predominant impact of selection pressure on CUB of tyrosinase genes was further supported by plots between ENC and GC 3 , and between ENC and CAI (Fig.…”
Section: Discussionmentioning
confidence: 90%